Exhaustive gold mineralizing processes of the Sanshandao gold deposit, Jiaodong Peninsula, eastern China: Displayed by hydrothermal alteration modeling. (1st November 2016) - Xu, Wen-Gang; Fan, Hong-Rui; Yang, Kui-Feng; Hu, Fang-Fang; Cai, Ya-Chun; Wen, Bo-Jie
Highlights: Hydrothermal alteration in the Sanshandao deposit can be produced by a single fluid. At low temperature, gold is easier to precipitate than that at high temperature. At high temperature, gold is probably hosted by pyrrhotite. Fluid cooling and mixing process can cause gold precipitation with similar mineral assemblages. Abstract: Sanshandao deposit, located in the western end of the Jiaodong Peninsula, is a typical altered-rock type gold deposit. The hydrothermal alteration in the deposit commences from potassic alteration with mineral assemblage mainly composed of K-feldspar and quartz, with minor sericite. The potassic alteration is followed by silicification that is always weakly developed in this district with minor sericite and gold-absent pyrite. As sericite content increases, the silicification alteration is gradually giving its way to sericitization. Fine sulfide crystals occur in this zone scattering in sericite and quartz matrix, which turns to be sulfidation as hydrothermal alteration proceeding. Gold mineralization is mainly associated with the sulfidation, predominantly hosted by pyrite. The latest hydrothermal alteration and veins consist of quartz-calcite-siderite(-ankerite) crosscutting the former alteration zones. Some auriferous sulfide-quartz veins fill the fractures in the alteration zones, but its gold reserve is limited. Geochemical modeling is applied to examine the hydrothermal alteration and gold precipitation processes in the Sanshandao deposit. Modeling shows that a gold-bearing fluid is potential to form an economic gold deposit via various paths, including fluid cooling, water-rock interaction, and fluid mixing with groundwater. The simulation results indicate that the auriferous quartz veins located in the alteration zones are probably generated by fluid cooling and mixing, whereas gold mineralization in the sulfide-sericite alteration stage is primarily caused by water-rock reaction that also produces the hydrothermal alteration following the potassic alteration. To evaluate the roles of water-rock interaction in gold mineralization at different temperatures, we execute simulations at T = 400 °C and 300 °C at pressure of 2 kbar. Gold precipitation at >400 °C is driven by strong water-rock reaction with low water/rock ratio, during which the gold precipitation is associated with pyrrhotite rather than pyrite, and thus the pyrite at this temperature scale is always gold-absent; at low temperature (∼300 °C), the water-rock interaction is effective to precipitate gold from the fluids, and gold mineralization links to pyrite precipitation. The comparison between these two simulations with different temperatures indicates that water-rock interaction at moderate temperature is prior to precipitate gold from hydrothermal fluid, which can be invoked to interpret the fact that gold mineralization is always intense in shallow level and host majority of gold reserve in this deposit. The modeling suggests that pyrrhotite should be paid more attention in future deep exploration since its ability to host certain gold budget at relatively high temperature.